Adapting a palliative care-focused cancer self- and family management intervention for use in Israel. (2nd August 2022) - Schulman-Green, Dena; Feder, Shelli L; Collett, David; Aaron, Eliana M.; Haron, Yafa; Eilon, Yael; Admi, Hanna
Abstract : Background: In Israel, there is a need to improve quality of life and health outcomes among patients and families facing cancer. Increasing awareness of, literacy about, and availability of palliative care may further this goal. Aims: This study aimed to adapt a palliative care-focused cancer self- and family management intervention developed in the US for use in Israel. Methods: The Managing Cancer Care (MCC) psycho-educational intervention is comprised of Managing Cancer Care: A Personal Guide (MCC-PT © ) for patients and Managing Cancer Care: A Caregiver's Guide (MCC-CG © ) for family caregivers. Following translation into Hebrew, an expert panel of Israeli nurses edited the MCC tool for cultural relevance. The authors then conducted qualitative interviews with patients with breast cancer and their family caregivers to obtain feedback. Data were analysed using qualitative content analysis. Findings: Following recommendations from Israeli experts in oncology and/or palliative care (n=3), the authors revised intervention content specific to the US healthcare system and culture. Patients' (n=13) and family caregivers' (n=10) reported MCC as attractive (70%, 80%), topically relevant (80%, 70%), and culturally appropriate, but felt that palliative care resources should be more Israel-specific. Conclusion: The MCC tool is acceptable to potential users, warranting further pilot-testing.